In view of standardization Part 2: Management of challenges in the initial treatment of burn patients in Burn Centers in Germany, Austria and Switzerland. Issue 2 (March 2017) - Ziegler, Benjamin; Hirche, Christoph; Horter, Johannes; Kiefer, Jurij; Grützner, Paul Alfred; Kremer, Thomas; Kneser, Ulrich; Münzberg, Matthias
Highlights: Burn-related issues of initial treatment of burn victims were evaluated. Discrepancies were found in the usage of colloidal fluids during resuscitation. Indications for primary tracheostomy and bronchoscopy were controversial issues. Diversifying treatment principles were found in topical wound treatment. Diagnostic measures were found to be managed in a similar way. Abstract: Introduction: Initial therapy of severe burns in specialized burn trauma centers is a challenging task faced by the treating multi-professional and interdisciplinary team. A lack of consistent operating procedures and varying structural conditions was recently demonstrated in preliminary data of our group. These results raised the question on how specific treatment measures in acute burn care are met in the absence of standardized guidelines. Material and methods: A specific questionnaire containing 57 multiple-choice questions was sent to all 22 major burn centers in Germany, Austria and Switzerland. The survey included standards of airway management and ventilation, fluid management and circulation, body temperature monitoring and management, topical burn wound treatment and a microbiological surveillance. Additionally, the distribution of standardized course systems was covered. Results: 17 out of 22 questionnaires (77%) were returned completed. Regarding volume resuscitation, results showed a similar approach in estimating initial fluid while discrepancies persisted in the use of colloidal fluid and human albumin. Elective tracheostomy and the need for bronchoscopy with suspected inhalation injury were the most controversial issues revealed by the survey. Topical treatment of burned body surface also followed different principles regarding the use of synthetic epidermal skin substitutes or enzymatic wound debridement. Less discrepancy was found in basic diagnostic measures, body temperature management, estimation of the extent of burns and microbiological surveillance. Conclusion: While many burn-related issues are clearly not questionable and managed in a similar way in most participating facilities, we were able to show that the most contentious issues in burn trauma management involve initial volume resuscitation, management of inhalation trauma and topical burn wound treatment. Further research is required to address these topics and evaluate a potential superiority of a regime in order to increase the level of evidence.